Zorba, o livre? A importância da liberdade para o projeto literário-filosófico de Nikos Kazantzákis - Santos, João Victor Rodrigues (2024)
Nikos Kazantzákis deals with universal themes throughout his literary and philosophical production: death, existential anguish and, above all, freedom. To search for it, a path followed by the Cretan author is one that necessarily involves the value given to the body and its capacity to signify and understand the world. Our research intends to focus on what we found problematic in Kazantzak's work: the search for freedom. Therefore, we adopt the following question as our central question: what is the role of the search for freedom for Nikos Kazantzákis' literary-philosophical project? We seek to investigate Vida e proezas de Aléxis Zorbás, his most popular and most translated work in Brazil, and investigate how we can think about the importance of freedom for the writer's literary-philosophical project, whether through dance or through an attempt to overcome nihilism. Thus, we propose a reading that reflects on the possible relationships between literature and philosophy and that investigates Aléxis Zorbás as an archetype of freedom. We adopted an exploratory bibliographic method, focusing on the literary investigation of Vida e proezas de Aléxis Zorbás, using the help of critical texts, commentators and/or theorists about the author and the novel. We developed our considerations on the issue raised based on the contributions of scholars such as Brandão (1996, 2001), Bernardes (2004, 2010), Pizarro (2008, 2015), Sartre (2004) and Nietzsche (2016, 2020). We consider that, by introducing us to the life and achievements of Aléxis Zorbás, Kazantzákis manages to reveal to us some of the elements that limit our creative capacity and, consequently, our existence, provoking us to reflection and the search for freedom, making us have awareness of the responsibility we have for our renunciations.